The Role of Five Facets of Mindfulness in a Mindfulness-Based Psychoeducation Intervention for People With Recent-Onset Psychosis on Mental and Psychosocial Health Outcomes - Chien, Wai Tong; Chow, Ka Ming; Chong, Yuen Yu; Bressington, Daniel; Choi, Kai Chow; Chan, Carmen Wing Han (Frontiers in Psychiatry, 2020)
Objective: This study aimed to examine how five facets of mindfulness may be associated with the changes in psychotic patients’ health outcomes after participating in a mindfulness-based psychoeducation group (MBPEG) program. Methods: Longitudinal follow-up data from two pragmatic randomized controlled trials of MBPEG for psychotic patients were used for this study. A total of 124 patients who completed the MBPEG program were included in this analysis. Patient outcomes (psychotic symptoms, functioning, insight into illness/treatment, subjective recovery) and five facets of mindfulness were assessed at baseline and six, 12 and 24 months post-intervention. Areas under the curve of individual outcomes in repeated-measures were computed using trapezoidal method, rescaled to the original possible range of the underlying variable and used for correlation and regression analyses. Results: All mean scores of the five facets increased across time and were significantly correlated with the improvements in all patient outcomes (p values ranged from <.001 to <.05), except ‘non-judging’ facet and symptom severity. Regression analyses revealed that only ‘observing’ and ‘acting with awareness’ were significantly associated with positive changes across all outcomes (increase in adjusted R2 ranged from 5.9% to 24.2%, p values <.001). Conclusions: Two facets of mindfulness, ‘observing’ and ‘acting with awareness’, were related to positive outcomes of psychotic patients after participating in the MBPEG. More efforts in addressing these two facets of mindfulness can be considered to increase the efficacy of mindfulness-based interventions in psychosis.